1982
DOI: 10.1159/000265195
|View full text |Cite
|
Sign up to set email alerts
|

G0/G1Arrest of Cell Proliferation in the Ocular Lens Prevents Development of Radiation Cataract

Abstract: Exposure of the eyes of young frogs and rats to X-rays (12–25 Gy) causes posterior cataracts to appear several weeks later. Hypophysectomized frogs do not develop these opacities, but hypophysectomized rats do. In the former, but not the latter animals, the operation completely stops lens mitosis, the epithelial cells being largely confined to the G₀/ G1 phase of the cell cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
(15 reference statements)
0
15
1
Order By: Relevance
“…Radiation-in duced cataracts belong to the so-called radia tion late effects which are observed stoch astically in large populations even after low-dose exposure. The main radiosensitive target of the lens is the germinative zone of the epithelium with its continuously divid ing lens epithelial cells [I, 2], This fact ex plains why young individuals having a higher mitotic rate are more radiosensitive than older ones [3,4] and species designed by a low rate of mitosis are less sensitive than others with high mitotic rates [5].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation-in duced cataracts belong to the so-called radia tion late effects which are observed stoch astically in large populations even after low-dose exposure. The main radiosensitive target of the lens is the germinative zone of the epithelium with its continuously divid ing lens epithelial cells [I, 2], This fact ex plains why young individuals having a higher mitotic rate are more radiosensitive than older ones [3,4] and species designed by a low rate of mitosis are less sensitive than others with high mitotic rates [5].…”
Section: Introductionmentioning
confidence: 99%
“…ASC or PSC) could be ascertained. Classically, radiation-induced cataracts are thought to form in the PSC area (18)(19)(20). However, it has also been reported that initial changes may occur in the anterior subcapsular region after treatment with high-LET radiation or high doses of low-LET radiation, and previous experiments conducted by our group showed that ASC opacification occurred at nearly the same time as PSC opacification (11,21,22).…”
Section: Measurement Of Lens Opacificationmentioning
confidence: 84%
“…Previous studies determined that the lens epithelium, and specifically the region where epithelial cell proliferation is concentrated, i.e. the germinative zone where IR effects are seen (12,30) and by preventing cell proliferation, IR-induced cataract is also prevented (31,32) . Given that the lens epithelium also is subject to circadian rhythm for cell proliferation (11) , why is the germinative zone of the lens especially sensitive to IR?…”
Section: Diurnal Changes In the Eye Lens: Cell Proliferation Melatonmentioning
confidence: 99%
“…Therefore timing IR exposures in the late afternoon or early evening would likely help reduce DNA damage and its effects upon the lens epithelium. Moreover, it is clear that reducing proliferation in the lens epithelium is radio-protective (31,32) . The occurrence and repair of DSBs in DNA differs between the germinative zone and the rest of the eye lens epithelium ( (30) and references therein).…”
Section: Diurnal Changes In the Eye Lens: Cell Proliferation Melatonmentioning
confidence: 99%